Improvement and Implementation of DRX in TD-LTE System - Qin Zhu; Xiaowen Li (Dianxin kexue)
With the enriching of mobile terminal business as well as the popularization of intelligent terminal, battery capacity of mobile terminal not only attracts so much attention in the field,but also encounters severe challenges. In the protocol of LTE system, in order to get the further more variety of business support and large amounts of data transmission, the DRX mechanism was taken as an important method to be introduced. Not only the different principles and mechanisms of DRX in different states including idle state and connection state were described in detail, but also the implementation process and the corresponding algorithm were proposed, Based on these, the algorithm of DRX in the connection state was optimized, which avoided invalid configuration resulting in the problem of increased signaling cost. Finally, complete implementation of the mechanism of DRX in different mobile business was given according to the different business characteristic, so that it improves the terminal consumption and signaling cost performance.